2017
DOI: 10.1093/toxsci/kfx174
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Environmentally Relevant Level of Arsenic on the Gut Microbiome and Its Functional Metagenome

Abstract: Multiple environmental factors induce dysbiosis in the gut microbiome and cause a variety of human diseases. Previously, we have first demonstrated that arsenic alters the composition of the gut microbiome. However, the functional impact of arsenic on the gut microbiome has not been adequately assessed, particularly at environmentally relevant concentrations. In this study, we used 16S rRNA sequencing and metagenomics sequencing to investigate how exposure to 100 ppb arsenic for 13 weeks alters the composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 59 publications
7
73
1
1
Order By: Relevance
“…The present study provides novel evidence that long-term exposure to multiple metals including As, Cd, Cu, Pb, and Zn is associated with alterations in the gut microbiome of people living in metal-polluted areas, especially for men. www.nature.com/scientificreports www.nature.com/scientificreports/ Metals such as As, Cd, and Cu, as well as excessive amounts of Zn, have been proven to reduce community diversity in previous studies 23,33,34 . Although no effect on α-diversity has been found, Pb was shown to change complexity (β-diversity) in an animal study 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides novel evidence that long-term exposure to multiple metals including As, Cd, Cu, Pb, and Zn is associated with alterations in the gut microbiome of people living in metal-polluted areas, especially for men. www.nature.com/scientificreports www.nature.com/scientificreports/ Metals such as As, Cd, and Cu, as well as excessive amounts of Zn, have been proven to reduce community diversity in previous studies 23,33,34 . Although no effect on α-diversity has been found, Pb was shown to change complexity (β-diversity) in an animal study 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Mice exposed for 2, 5, or 10 weeks to 0, 10, or 250 ppb arsenite (As III ) showed changes in the colonic microbial population, metabolic phenotype, and levels of metabolites in the tissue and serum (37). Another study showed that 100 ppb arsenic exposure for 13 weeks changed the gut microbial composition and altered important microbial functional pathways (carbohydrate metabolism [especially pyruvate fermentation], short-chain fatty acid synthesis, and starch utilization) that could influence host metabolism (38). Moreover, child gut microbiota exhibit high levels of As III , the more toxic form of arsenic, which could result in increased health risk (39).…”
mentioning
confidence: 99%
“…As we mentioned previously, previous studies indicated that increasing the intake of folate, riboflavin and cobalamin could protect people from As-induced diseases, which is related to As susceptibility [90, 91]. Our recent study found that in the low As-exposed gut microbiome, vitamin synthetic genes were largely enriched, suggesting a potential protective response to As exposure [130]. Likewise, choline is an essential nutrient and can be transformed into betaine to remethylate homocysteine in the one-carbon metabolism pathway [149].…”
Section: Gut Microbiome and As Susceptibilitymentioning
confidence: 80%
“…First, accumulating evidence indicates that gut microbiota activities influence the bioaccessibility and biotransformation of As, which could influence the toxic effects of As on the host body [128, 129]. Second, studies show that As exposure can perturb the normal composition and functional gene profile of the gut microbiome and thus could potentially affect host health [10, 130]. As such, both of these aspects could influence the individual susceptibility to As-induced diseases.…”
Section: Gut Microbiome and As Susceptibilitymentioning
confidence: 99%